Architect of European unity : memoirs, 1911-1986 - Marjolin, Robert (London : Weidenfeld and Nicolson, 1989)
This is a remarkable book by an exceptional man of both thought and action who show himself also to be an accomplished writer. Robert Marjolin's life spans the most important events in the history of this century after the first world war period.
Translation of: Le travail d'une vie.
Includes bibliographical references and index.
aia 24/01/2019
Loans
Keywords: Marjolin, Robert; Statesmen; Economists; Petroleum industry and trade; France; France